Microenvironment of a tumor-organoid system enhances hepatocellular carcinoma malignancy-related hallmarks. (3rd July 2017) - Wang, Yang; Takeishi, Kazuki; Li, Zhao; Cervantes-Alvarez, Eduardo; Collin de l'Hortet, Alexandra; Guzman-Lepe, Jorge; Cui, Xiao; Zhu, Jiye
ABSTRACT: Organ-like microenviroment and 3-dimensional (3D) cell culture conformations have been suggested as promising approaches to mimic in a micro-scale a whole organ cellular functions and interactions present in vivo. We have used this approach to examine biologic features of hepatocellular carcinoma (HCC) cells. In this study, we demonstrate that hepatocellular carcinoma (HCC) cells, fibroblasts, endothelial cells and extracellular matrix can generate organoid-like spheroids that enhanced numerous features of human HCC observed in vivo. We show that the addition of non-parenchymal cells such as fibroblast and endothelial cells is required for spheroid formation as well as the maintenance of the tissue-like structure. Furthermore, HCC cells cultured as spheroids with non-parenchymal cells express more neo-angiogenesis-related markers (VEGFR2, VEGF, HIF-α), tumor-related inflammatory factors (CXCR4, CXCL12, TNF-α) and molecules-related to induced epithelial-mesenchymal transition (TGFβ, Vimentin, MMP9) compared with organoids containing only HCC cells. These results demonstrate the importance of non-parenchymal cells in the cellular composition of HCC organoids. The novelty of the multicellular-based organotypic culture system strongly supports the integration of this approach in a high throughput approach to identified patient-specific HCC malignancy and accurate anti-tumor therapy screening after surgery.